Large-scalable fabrication of liquid metal-based double helix core-spun yarns for capacitive sensing, energy harvesting, and thermal management. (February 2023) - Fu, Chiyu; Tang, Wenyang; Miao, Ying; Xu, Ao; Nilghaz, Azadeh; Xu, Weilin; Dong, Kai; Su, Bin; Xia, Zhigang
Abstract: Yarn-based flexible sensors are the crucial components of intelligent wearable electronics. However, the mass fabrication of high-performance yarn sensors with multifunctional and wear-comfortable remains a challenge. Herein, liquid metal-based double helix core-spun yarns (DHCYs) can be massively produced via a facile friction core-spinning for human motion monitoring, energy harvesting and thermal management. Due to the stable double helix and hierarchical structure, the yarn and its fabric exhibit combined superiority of flexibility, breathability and washability. The yarn strain sensor demonstrates a good workable range (100%), high sensitivity, ultra-low hysteresis and high durability (6000 cycles). For energy harvesting, the plain-woven fabric exhibits the excellent triboelectric performance of 50 V open-circuit voltage (VOC ), 500 nA short-circuit current (ISC ), and 100 nC short-circuit transferred charge (QSC ). Moreover, owing to the high electrical conductivity of liquid metal, the DHCYs present a fast temperature response and achieve a stabilized temperature from 16 ℃ to 45 ℃ within 80 s under 6 V. As proof of concept, we demonstrate the electrothermochromism and heat preservation of DHCYs, indicating its great potential in smart textiles, wearable devices and human-machine interfaces. Graphical Abstract: ga1 Highlights: A liquid metal based double helix core-spun yarn (DHCY) is massively produced via a facile friction core-spinning. The proposed double helix core-sheath structural yarns have excellent flexibility, breathability and washability. The DHCY and fabric are demonstrated as a capacitive strain sensor, energy harvester, and thermal manager.